Sinkronisasi Perdais Yogyakarta Tentang Pemeliharaan dan Pengembangan Kebudayaan dengan Undang-Undang Pemajuan Kebudayaan - Herman Hendrik (Badan Penelitian dan Pengembangan Provinsi Sumatera Utara, 2023)
This paper describes the results of legal synchronization analysis of the Special RegionalRegulation Number 3 of 2017 concerning the Maintenance and Development of Culture (PerdaisNo. 3 of 2017) with Law Number 5 of 2017 concerning the Advancement of Culture (UUPemajuan Kebudayaan). The analysis is based on the existence of a number of mandates fromthe Law for the Advancement of Culture to local governments. The existence of regionalregulations (perda) of culture is important as the legal basis for cultural policies in the region.Given that theoretically, a regional regulation should not conflict with the regulations that arehierarchically above it, it is important for this regional regulation to be in line with the Law for theAdvancement of Culture. To achieve this, a normative legal study was carried out with a synchronization approach to the Perdais Yogyakarta No. 3 of 2017 with the Law for theAdvancement of Culture. Based on the synchronization results obtained, it was revealed thatsystematically the number of chapters in the Perdais Yogyakarta No. 3 of 2017 is more than theLaw for the Advancement of Culture, but the number of articles is much less. It has also beendescribed that the Law for the Advancement of Culture has mandated a number of matters tolocal governments. In this regard, Perdais Yogyakarta No. 3 of 2017 seeks to regulate thesemandates in its articles. In this regional regulation, most of the mandates of the Law for theAdvancement of Culture to local governments have been regulated by the said regionalregulation. This reflects the misalignment of cultural policy concepts between the central andlocal governments.Keywords: culture, cultural advancement, regional law, cultural polic